The Antibiotic Knowledge, Attitudes, and Behaviors of Patients Purchasing Antibiotics without Prescription: Results of National Survey - Svetlana Rachina; Polina Zakharenkova; Roman Kozlov; Ivan Palagin; Daria Mamchich; Daria Strelkova (Advances in Public Health)
Background. The inappropriate and overuse of antimicrobials is a problem worldwide. To target future interventions, a thorough understanding of current behavior reasons is needed. The aim of the study was to explore antibiotic knowledge, attitudes, and behaviors among patients residing in Russia. Methods. In total, 149 semistructured interviews were carried out with respondents using antibiotics without prescriptions. Interviews were used to assess participants’ practices to treat symptoms of a confirmed/suspected infectious disease and their behaviors, knowledge, and attitudes toward the use of antimicrobials. A directed content analysis was applied. Results. Despite regulation, inappropriate use of antibiotics is a common practice. Knowledge on the mechanism of action and indications for the use of antibiotics was generally low. However, self-diagnosis, self-treatment with antimicrobials, and attempts to purchase antibiotics in pharmacies with no prescription were quite common. Family members and friends were involved in decisions about treatment strategy. Time spent for the doctor’s visit, fear to be exposed to additional infections in outpatient clinics/hospitals, previous experience with antimicrobial self-treatment, and “loyal” policy of selling antibiotics influenced the respondents’ decisions of not going to the doctor. COVID-19 made an impact on antimicrobial self-treatment: there was a substantial complexity in contacting a medical healthcare provider. Most of the respondents did not pay much attention or even noticed informational materials on the proper use of antibiotics. Conclusion. Self-treatment with antibiotics in Russia exists. Conducted information campaigns were not effective enough as the low level of knowledge about antimicrobials and antimicrobial resistance was revealed by the present study.